Tax effects of termination of economic activity in terms of income tax and tax procedure - Szumlakowski, Roman (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
On the basis of tax procedure the tax legislator introduces the concept of securing the implementation of tax liabilities resulting from the termination of a business through the effective use of the institution of solidarity debtor pursuant. The termination of economic activity is understood as a physical liquidation of a business rather than its subjective transformation, which may constitute the continuation of economic activity in a new organizational and legal form. This activity of the tax legislator consists in ensuring the implementation of tax liabilities by the tax bodies, which reflects the legislator’s position in the relationship between law and socio-economic development. The legislator strongly emphasised effective implementation of tax liabilities for the benefit of the state budget, which constitutes a compromise between certainty and flexibility of the tax law.
Keywords: economic efficiency; economic activity; tax procedure; entrepreneur; commercial companies; income taxes